Innovation In Thematic Learning Through The Use Of The Surrounding Environment At Madrasah Ibtidaiyah Nurfitri, North Sumatra - Mursal Aziz; Muhammad Hasbie Ashshiddiqi; Citra Resmi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study aims to analyze thematic learning innovation through the utilization of the surrounding environment as a learning resource at Madrasah Ibtidaiyah Nurfitri, North Sumatra. A qualitative descriptive approach was employed, with data collected through observations, interviews, and documentation involving the principal, teachers, and students. Data were analyzed using data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings reveal that the use of the surrounding environment transformed thematic learning into a more contextual, active, and meaningful process. Teachers integrate natural and social environments into learning activities through observation, discussion, and direct experiences outside the classroom. This strategy enhances students' motivation, participation, understanding, and social skills while fostering positive character values ​​such as environmental awareness, cooperation, and responsibility. Despite challenges related to time constraints, student safety, and teacher preparedness, the study confirms that the surrounding environment serves as an effective learning resource for supporting thematic learning in Madrasah Ibtidaiyah.